Antioxidant, Anti-Oral Cancer, and Antimicrobial Activity of Medicinal Plant Extracts: Development of Mouthrinse Formulations - Suree Nanasombat (Trends in Sciences, 2023)
Nowadays, there is growing interest in using medicinal plants as antimicrobial agents to treat microbial infections in the oral cavity. This study was aimed to evaluate phytochemical properties, anti-oral cancer and antimicrobial activity against C. albicans and some potential oral lactic acid bacteria (Lactobacillus casei and Lactobacillus plantarum). Plant extracts including Cinnamomum verum (cinnamon), Acorus calamus (sweet flag), Hibiscus sabdariffa (roselle), Zingiber officinale (ginger) and Alpinia officinarum (lesser galangal) were tested and used to formulate mouthrinses for oral health care. Cinnamon extract possessed the highest phenolic, flavonoid and tannin content, and antioxidant activity (1,152.58 mg ascorbic acid equivalent/g by phosphomolybdenum assay and 39.64 % nitric oxide radical scavenging activity), while roselle extract had the highest total alkaloids. Only lesser galangal extract displayed anti-oral cancer activity with 97.83 % cytotoxicity. High performance liquid chromatography (HPLC) analysis revealed the presence of galangin and kaempferide in the lesser galangal rhizome extract. The cinnamon extract showed the strongest inhibitory activity against Candida albicans (4 mg/mL MIC). Cinnamon extract (24 mg/mL) and cinnamaldehyde (0.08 mol/L) exhibited the best killing effect and the highest cellular protein leakage in C. albicans. In addition, these plant extracts were used to develop mouthrinse formulations. The extracts of cinnamon and ginger at 10 % in mouthrinse formulations could strongly inhibit the growth of C. albicans. In comparison, 8 and 10 % roselle extracts showed the best inhibitory effect against Lactobacillus casei. In summary, cinnamon and lesser galangal were potential plants with antimicrobial, antioxidant, anti-biofilm and anti-oral cancer activities, and thus can be utilized to formulate oral care products. HIGHLIGHTS Lesser galangal was found to be a prominent anti-oral cancer plant Cinnamon was shown to be an interesting anti-Candida albicans plant Cinnamon, ginger and roselle extracts at 10 % in mouthrinse formulations exhibited strong antimicrobial activity. These plants can be used to incorporate into oral care products for treatment and prevention of oral diseases GRAPHICAL ABSTRACT
Keywords: Medicinal Plants and Neuroprotection; Phytochemicals and Medicinal Plants; Oral microbiology and periodontitis research